2021
DOI: 10.18632/aging.203131
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes (CNT)-loaded ginsenosides Rb3 suppresses the PD-1/PD-L1 pathway in triple-negative breast cancer

Abstract: Carbon nanotubes (CNTs), as advanced nanotechnology with specific properties and structures, have presented practical drug delivery properties. Ginsenoside Rg3 is a component of puffed ginseng and demonstrates anti-cancer activities. To explore the effect of CNTs-loaded Rg3 (Rg3-CNT) on the PD-1/PD-L1 signaling and the development of triple-negative breast cancer (TNBC). Our data revealed that Rg3 inhibited the cell viability of TNBC cells, in which Rg3-CNT further enhanced this effect in the system. Similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Moreover, ginsenoside Rh2 can enhance CD4 + and CD8a + T‐cell infiltration in the tumor tissues of melanoma (B16‐F10)‐bearing mice, and ginsenoside Rg1 can increase CD4 + T‐cell proliferation and activity in mice 131,174 . Importantly, carbon nanotubes‐loaded ginsenoside Rg3 can reduce PD‐1 expression in activated T cells and attenuate PD‐L1 expression in triple‐negative breast cancer cells, thereby stimulating the production of IFN‐γ, IL‐2, IL‐9, IL‐10, IL‐22, and IL‐23 from the activated T cells and attenuating the MDA‐MB‐231 breast cancer cell growth in vivo 130 . However, it is not clear whether ginsenosides target CTLA‐4.…”
Section: Potential Natural Products From Herbal Medicines With Immuno...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ginsenoside Rh2 can enhance CD4 + and CD8a + T‐cell infiltration in the tumor tissues of melanoma (B16‐F10)‐bearing mice, and ginsenoside Rg1 can increase CD4 + T‐cell proliferation and activity in mice 131,174 . Importantly, carbon nanotubes‐loaded ginsenoside Rg3 can reduce PD‐1 expression in activated T cells and attenuate PD‐L1 expression in triple‐negative breast cancer cells, thereby stimulating the production of IFN‐γ, IL‐2, IL‐9, IL‐10, IL‐22, and IL‐23 from the activated T cells and attenuating the MDA‐MB‐231 breast cancer cell growth in vivo 130 . However, it is not clear whether ginsenosides target CTLA‐4.…”
Section: Potential Natural Products From Herbal Medicines With Immuno...mentioning
confidence: 99%
“…131 , 174 Importantly, carbon nanotubes‐loaded ginsenoside Rg3 can reduce PD‐1 expression in activated T cells and attenuate PD‐L1 expression in triple‐negative breast cancer cells, thereby stimulating the production of IFN‐γ, IL‐2, IL‐9, IL‐10, IL‐22, and IL‐23 from the activated T cells and attenuating the MDA‐MB‐231 breast cancer cell growth in vivo. 130 However, it is not clear whether ginsenosides target CTLA‐4.…”
Section: Potential Natural Products From Herbal Medicines With Immuno...mentioning
confidence: 99%
“…Further, it was observed that Rg3 impaired the upregulation of PD-L1 in activated T-cells. Moreover, treatment with CNTs reduced the levels of interleukins (IL-2, Il-9, Il-10, IL-22, and IL-23) and interferons (IFN-ϒ), thereby attenuating the PD-L1 signaling pathway [ 278 ].…”
Section: Nanotechnology: Cavalry For Tnbc Therapymentioning
confidence: 99%
“…Recently, Luo et al . designed a nanosystem composed of MWNTs-loaded ginsenoside Rg3 (Rg3-CNT) for triple-negative breast cancer (TNBC) treatment, which firstly demonstrated the new function of Rg3-CNT in elevating the therapeutic efficacy of Rg3 against TNBC through the inhibition of PD-1/PD-L1 axis, providing a potential strategy for TNBC treatment through immunotherapy [ 78 ]. In their study, Rg3-CNT was found to reduce PD-L1 expression and PD-L1 upregulation induced by IFN-γ in TNBC cells, meanwhile, PD-1 expression, PD-1/PD-L1 signaling were also suppressed, which remarkably inhibited the TNBC cell growth in vivo.…”
Section: Carbon Nanotubes In Cancer Treatmentmentioning
confidence: 99%